High expression of the tumor suppressor protein ITIH5 in cholangiocarcinomas correlates with a favorable prognosis - Dreyer, Verena J.; Shi, Jia-Xin; Rose, Michael; Onyuro, Maureen T.; Steib, Florian; Hilgers, Lars; Seillier, Lancelot; Dietrich, Jana; Riese, Janik; Meurer, Steffen K.; Weiskirchen, Ralf; Neumann, Ulf; et al. (Cancers, 2024)
Background: Cholangiocarcinoma (CCA) are aggressive bile duct cancers with a poor prognosis for which there are only few established prognostic biomarkers and molecular targets available. The gene ITIH5, a known class II tumor suppressor gene (C2TSG), encodes a secreted protein of the extracellular matrix mediating tumor suppressive properties. Recently, it was surprisingly found that the ITIH5 protein is specifically upregulated in CCAs and that ITIH5 detection in blood could be an excellent liquid biopsy marker for indicating the presence of a CCA tumor in a patient. We therefore investigated whether patients with CCAs with abundant versus low ITIH5 protein expression also differ in their prognosis. Methods: To clarify this question, a large CCA cohort (n = 175) was examined using immunohistochemistry on a tissue microarray (TMA). Results: Abundant ITIH5 expression in CCA was associated with favorable survival, a low UICC stage and the absence of perineural invasion (PNI). Conclusions: ITIH5 has biomarker potential not only for the early detection of CCA from blood-based liquid biopsies but also as a prognostic tissue biomarker for risk stratification. Our results suggest that the upregulation of ITIH5 is particularly abundant in intrahepatic CCAs (iCCA). The mechanisms mediating the strong initial upregulation of ITIH5 during the oncogenic transformation of bile duct cells are still unclear.